The relationship between remnant cholesterol and the risk of testosterone deficiency in US adults: a cross-sectional study based on the NHANES database - Mei, Yangyang; Chen, Yiming; Wang, Xiaogang; Xu, Renfang; Feng, Xingliang (Frontiers in Endocrinology, 2024)
Background: Testosterone deficiency (TD) is an urgent health issue that requires attention, associated with various adverse health outcomes. Remnant cholesterol (RC) has emerged as a potential biomarker for cardiovascular risk, but its relationship with testosterone levels has not been thoroughly investigated. This study aims to explore the association between RC and TD in adult American males using data from the National Health and Nutrition Examination Survey (NHANES).This cross-sectional study utilized data from three NHANES cycles (2011)(2012)(2013)(2014)(2015)(2016), including 2,848 adult male participants. RC was calculated as total cholesterol minus high-density lipoprotein cholesterol (HDL) and low-density lipoprotein cholesterol (LDL). TD was defined as total testosterone levels below 300 ng/dL. Multivariable linear and logistic regression analyses, as well as smooth curve fitting and generalized additive models, were performed to assess the associations between RC and total testosterone levels and TD, adjusting for potential confounders.Subgroup analyses were conducted based on age, BMI, smoking status, diabetes, hypertension, CVD, and chronic kidney disease (CKD).Results: Higher RC levels were significantly associated with lower total testosterone levels (β = -53.87, 95% CI: -77.69 to -30.06, p<0.001) and an increased risk of TD (OR = 1.85, 95% CI: 1.29 to 2.66, p=0.002) in fully adjusted models. When RC was analyzed as quartiles, participants in the highest quartile (Q4) had significantly lower total testosterone levels (β = -62.19, 95% CI: -93.62 to -30.76, p<0.001) and higher odds of TD (OR = 2.15, 95% CI: 1.21 to 3.84, p=0.01) compared to those in the lowest quartile (Q1). Subgroup analyses revealed consistent associations across different age groups, particularly strong in participants over 60 years, and in never smokers. The associations remained significant in both hypertensive and non-hypertensive groups, as well as in those with and without CKD. No significant interactions were found across subgroups.This study demonstrates a significant inverse association between RC levels and total testosterone levels, along with a positive association with the risk of TD. These findings suggest that RC could serve as a valuable biomarker for early identification of individuals at risk for TD. Future longitudinal studies are needed to confirm these findings and explore the underlying mechanisms.